Kewajiban Memberi Biaya Penghidupan Oleh Suami Kepada Mantan Istri (Studi Komparasi Antara Hukum Islam dan Hukum Perdata) - Muh. Fahrul; Saharuddin Saharuddin; Lia Trizza Firgita Adhilia (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to know and understand the husband's obligation to provide living expenses to the ex-wife and the rights of the ex-wife after divorce. The type of research in this study is Normative-empirical. The results showed the ex-husband's obligations and the wife's rights after the divorce with the provisions attached to it as previously explained. For example, there are things that make the ex-wife get the right to provide whether it is Iddah, Mut'ah, or Lampau, but there are also things that cause the ex-wife to be not entitled to that right.